THE INFLUENCE OF DISCIPLINE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN THE HUMAN RESOURCES BUREAU AND THE SECRETARIAT APPARATUS OF THE HOUSE OF REPRESENTATIVES GENERAL - Khoerul Nur Rizqi; Lady Diana Warpindyastuti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
In public sector organizations, employee performance is a crucial element determining the success of and the achievement of institutional goals. Attendance, discipline, and work ethusiasm are key indicators in assesing human resource effectiveness, particularly in goverment agencies. This study aims to determine the influence of discipline and work motivation on employee performance at the Bureau of Human Resources and Apparatus of the Secretariat General of the Indonesia House of Representatives. Employee performance is a crucial factor in ensuring organizational effectiveness and is influenced by the level of individual discipline and motivation in carrying out their duties. This study used a quantitative statistical approach with a survey method through the distribution of questionnaires to 80 respondents consisting of Civil Servants (PNS), Government Employees with Work Agreements (PPPK), Support System Personnel (TSP), and Pramubakti. Data analysis techniques used included validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, f-tests, and coefficient of determination tests using SPSS version 27 software. The results of the analysis indicate that discipline and work motivation have a positive and significant effect on employee performance, both partially and simultaneously.